Women’s Activism in Twentieth-Century Britain - Bartley, Paula. author. aut Link
XII, 286 p. 23 illus., 10 illus. in color.
Keywords: This book serves as an introduction to the extraordinary diversity of women’s activism. Paula Bartley's original research is supported by a range of writing to provide a powerful impression of the actions taken by groups of women from across the social and political spectrum, making the book invaluable to both students and interested readers. These women set out to make a difference to their locality, their country and sometimes the world. The story of women’s activism embodies stimulating accounts of progress and reversals, of commitment and uncertainty, of competing rights and challenging wrongs. The story of women’s activism is not tidy or well-ordered. It is messy and unorthodox. And full of surprises. Paula Bartley is a feminist historian who has written widely on, and promoted, women’s history. Her books include Ellen Wilkinson (2014), Queen Victoria (2016) and Labour Women in Power: Cabinet Ministers in the Twentieth Century (Palgrave, 2019). She is a former judge and Chair of the Women’s History Network book prize. “Paula Bartley's fresh approach tells a multi-dimensional story of women’s political engagement. She synthesizes women’s activism from points across the political spectrum, including both far left and far right women, and the many in between, acknowledging that not all women’s political engagement has been ‘progressive’ or feminist. Her own insight and experience add depth and authenticity to this valuable study." ---Julie Gottlieb, Professor of History, University of Sheffield, UK “This book is a really enjoyable read. It also reminds us that it is not powerful men, or even women, that make history but activists that create the waves. And it is also clear, not all women are progressive.” ---Clare Short, Former Labour MP and Secretary of State for International Development “A compelling history of the women who marched, fasted and stormed bastionsof male politics and society for suffrage, workers’ rights, control over their bodies, even the right to serve in bars. Paula Bartley reminds us once again of their courage and fortitude, of campaigns big and small, and how much we owe these pioneers.” ---Shrabani Basu, journalist, historian, and best-selling author.